Advanced Amperometric Microsensors for the Electrochemical Quantification of Quercetin in Ginkgo biloba Essential Oil from Regenerative Farming Practices - Elena Oancea; Ioana Adina Tula; Gabriela Stanciu; Raluca-Ioana Ștefan-van Staden; Jacobus (Koos) Frederick van Staden; Magdalena Mititelu (Metabolites)
In this study, we present a novel approach using amperometric microsensors to detect quercetin in cosmetic formulations and track its metabolic behavior after topical application. This method offers a sensitive, real-time alternative to conventional techniques, enabling the detection of quercetin’s bioavailability, its transformation into active metabolites, and its potential therapeutic effects when applied to the skin. Quercetin (Q) is a bioactive flavonoid known for its potent antioxidant properties, naturally present in numerous plants, particularly those with applications in cosmetic formulations. In response to the growing interest in developing novel plant-based dermo-cosmetic solutions, this study investigates the electrochemical detection of quercetin, a ketone-type flavonoid, extracted from Gingko biloba essential oil. Three newly designed amperometric microsensors were developed to assess their efficacy in detecting quercetin in botanical samples. The sensor configurations utilized two forms of carbon material as a foundation: graphite (G) and carbon nanoparticles (CNs). These base materials were modified with paraffin oil, chitosan (CHIT), and cobalt(II) tetraphenylporphyrin (Co(II)TPP) to enhance sensitivity. Differential pulse voltammetry (DPV) served as the analytical method for this investigation. Among the sensors, the CHIT/G–CN microsensor exhibited the highest sensitivity, with a detection limit of 1.22 × 10−7 mol L−1, followed by the G–CN (5.64 × 10−8 mol L−1) and Co(II)TPP/G–CN (9.80 × 10−8 mol L−1) microsensors. The minimum detectable concentration was observed with the G–CN and CoP/G–CN microsensors, achieving a threshold as low as 0.0001 μmol L−1. Recovery rates and relative standard deviation (RSD) values averaged 97.4% ± 0.43, underscoring the sensors’ reliability for quercetin detection in botanical matrices.